Quantitative determination of ketotifen in drug dosage forms by spectrophotometric method - Zagorodniy, S. L.; Monaykina, Y. V.; Vasyuk, S. O.; Васюк, Світлана Олександрівна (My University, 2015)
ABSTRACT A new spectrophotometric method for the quantitative determination of ketotifen in pharmaceutical formulations, such as tablets and capsules, has been developed. This method is based on the formation of yellow complex as a result of the reaction between ketotifen and bromocresol purple (5',5"-dibromo-ocresolsulfophthalein) with maximum absorption at 399 nm in acetone. The proposed method is valid according to the validation requirements of Ukrainian Pharmacopeia. According to the experimental data, the technique can be correctly reproduced and it is suitable for routine quality control.
Keywords: ketotifen; quantitative determination; spectrophotometric method; bromocresol purple